INTRAVENOUS PARACETAMOL INFUSION VERSUS INTRAMUSCULAR PETHIDINE AS LABOUR ANALGESICS - Nasir, Sallama Kamel; Ibrahim, Hala Shaaban (Journal of Sulaimani Medical College, 2019)
Background Labour is one of the most painful and stressful events in life. The intensity of pain experienced by women in labour has been found to affect the progress of labour, fetal well-being and maternal psychology. Intramuscular pethidine is one of most common drugs used for labour analgesia. Paracetamol may be used as alternative to pethidine as labour analgesia. Objective To compare the efficacy and adverse effects of intravenous paracetamol versus intramuscular pethidine hydrochloride as analgesia in the 1st stage of labour. Patients and Methods This is a single-blinded prospective-randomized study conducted in Sulaimani maternity teaching hospital over a period of six months starting from the 1st of December 2017 till 31st of May 2018. The study included 200 primigravidae women with term uncomplicated pregnancy in their active phase of labour. After taking informed consent, the women were randomly distributed into two groups, one hundred women received 1000mg paracetamol by intravenous infusion, and the other one hundred women received 100 mg pethidine intramuscularly. The primary outcome was the efficacy of the drug to provide adequate analgesia in labour. Pain intensity before administering drug was recorded by Mc Gills pain intensity scale, then at the 1sthr, and in the 3rdhr after drug administration. The secondary outcomes included the presence of adverse maternal effects, mode of delivery and fetal Apgar scores at 1st and 5th minutes. Results The mean of pain score was low in both groups after 1h of drug administration but it was significantly lower in the pethidine group. Also at 3h of drug administration the mean pain score was significantly much lower in pethidine group compared to the paracetamol group (p -value=0.001). The maternal and neonatal side effects were significantly higher in the pethidine group compared to the paracetamol group (P value= 0.001) Conclusions Intramuscular pethidine is more effective than intravenous paracetamol in relieving pain during the 1st stage of labour. But the use of paracetamol causes less maternal and neonatal side effects than pethidine.
Keywords: Labour pain; Analgesia; Intramuscular pethidine; Intravenous paracetamol